A tale of two cities: Singapore and Hong Kong after the Asian financial crisis. - Chua, Xiaoying. (2008)
This project seeks to explore the economic factors that account for the differing economic situations in Singapore and Hong Kong since the Asian Financial Crisis. The EGOIN framework is used to evaluate the contribution of each agent towards the countries’ recovery and provide a projection of their economic outlook.